IMPLEMENTATION OF URBAN FARMING PROGRAM IN SURABAYA INDONESIA FOR DECREASE POVERTY AND EFFORT TO CREATE GREEN AREA - Endang Yektiningsih; Sigit Dwi Nugroho (UPT Penerbitan Universitas Jember, 2012)
Almost all countries in the world have same problem of how to manage urban areas that have a lot of people, including the poor people. Urban Farming is one solution of thisproblem, but not simple in implementation. The aim of this research is to determine theimpact of urban farming program implementation on environment, economic, social andcultural of poor households, and also to analyze factors affecting the motivation of poorpeoples to follow urban farming program. Through random sampling method wedetermined the amount of samples, as many as 99 poor households. While the method ofanalysis used in this study is descriptive, correlation, and multiple regression model. Theresult showed that urban farming program has multiple benefits, creating a green area,which means maintaining a healthy living environment, improve the social relations ofsociety, but no relationship with culture of the poor peoples. By the multiple reressionanalyzis showed result that only leisure time factor affected to the motivation of poorhouseholds in Surabaya’s urban farming program.